Resolusi Konflik Etnis-Teologis: Pembacaan Social Identity Theory atas Efesus 2:11-22 - Ivana Aimee Djuharto; Liu Wisda (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. This study re-examines the ethnic-theological conflict in Ephesians 2:11-22 through the lens of Social Identity Theory (SIT), aiming to reveal the dynamics of intergroup conflict and its resolution. The research was aimed to analyze the text by identifying the in-group (non-Christian Jews) and out-group (non-Christian Gentiles), their conflicting beliefs/norms, and the resolution strategy offered by the author. The analysis demonstrates that the conflict arose from divergent ethnic-theological norms (circumcision, The Law). The author's resolution strategy is identified as recategorization into a new superordinate identity (